Hubungan On-Fomo dengan Netiquette Mahasiswa Jurusan Bimbingan dan Konseling Universitas Lambung Mangkurat: The Relationship Between On-Fomo and Netiquette of Guidance and Counseling Students at Lambung Mangkurat University - Yunita Ani Rajatman; Eklys Cheseda Makaria; Ali Rachman (ITScience (Information Technology and Science), 2025)
Generation Z has a close relationship with the internet, leading to the emergence of various new habits, such as the fear of missing out (FoMO) behavior. In the digital context, this behavior is referred to as Online Fear of Missing Out (On-FoMO), which is the tendency to always stay connected to online activities due to the fear of missing out on information or trening topics. In social media usage, there are also norms or ethical rules that serve as boundaries for individuals' actions, commonly known as netiquette. Based on interviews conducted with guidance and counseling students, they admitted to experiencing FoMO, particularly in social media activities such as monitoring social media, adopting speech styles, following jokes, and keeping up with the latest news. However, in internet activities, some of them believe that ethical considerations are necessary, while others admitted to having acted outside these ethical boundaries. This study aims to analyze the relationship between On-FoMO and netiquette among students of the Guidance and Counseling Department at Lambung Mangkurat University. The results indicate that the majority of respondents have low to moderate levels of On-FoMO, whereas their netiquette levels tend to be high. Correlation analysis shows a value of r = -0.090 with p = 0.140 (>0.05). These results indicate that there is no significant relationship between On-FoMO and netiquette. Although there is a tendency for higher On-FoMO levels to correlate with lower netiquette, this relationship is very weak and cannot be concluded as significant. These findings suggest that other faktors influence netiquette more than On-FoMO levels. Therefore, future researchers are encouraged to include additional variabels to gain a deeper understanding of netiquette, such as digital awareness, social norms, self-control, and social media experience.